2022
DOI: 10.1002/ctm2.940
|View full text |Cite
|
Sign up to set email alerts
|

N6‐methyladenosine demethylase ALKBH5 suppresses colorectal cancer progression potentially by decreasing PHF20 mRNA methylation

Abstract: ALKBH5 expression is down-regulated in CRC and plays a crucial tumor suppressive role.• ALKBH5 inhibits the stability of PHF20 mRNA by removing the m 6 A modification.• Targeting the ALKBH5-mediated m 6 A modification of PHF20 mRNA may be a promising therapeutic strategy for intervention and treatment of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
(92 reference statements)
0
18
0
Order By: Relevance
“…Previous research has demonstrated the function of m 6 A modification, especially the “writers” METTL14 and “erasers” ALKBH5, in CRC. For example, in a study by Zhang et al, the author showed that ALKBH5 prevents CRC progression by blunting PHF20 mRNA methylation . Li et al demonstrated that ALKBH5 sensitized the tumor to anti-PD-1 therapy by inducing lactate and suppressive immune cell accumulation .…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has demonstrated the function of m 6 A modification, especially the “writers” METTL14 and “erasers” ALKBH5, in CRC. For example, in a study by Zhang et al, the author showed that ALKBH5 prevents CRC progression by blunting PHF20 mRNA methylation . Li et al demonstrated that ALKBH5 sensitized the tumor to anti-PD-1 therapy by inducing lactate and suppressive immune cell accumulation .…”
Section: Resultsmentioning
confidence: 99%
“…found that ALKBH5 facilitated the malignant behaviour of CRC via modulating lncRNA NEAT1 demethylation 33 . While a most recent study identified that ALKBH5 could suppress CRC progression by decreasing PHF20 mRNA stability via an m6A‐dependent pathway 34 . These controversial results reflected that the consequences of aberrant m6A deposition may depend on the cancer heterogeneity, and even in the same tumour, it may depend on specific cell types or dysregulation of the downstream target genes and signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…33 While a most recent study identified that ALKBH5 could suppress CRC progression by decreasing PHF20 mRNA stability via an m6A-dependent pathway. 34 These controversial results reflected that the consequences of aberrant m6A deposition may depend on the cancer heterogeneity, and even in the same tumour, it may depend on specific cell types or dysregulation of the downstream target genes and signalling pathways. In our research, we screened the expression of ALKBH5 in CRC from the cellular to tissue levels and further to clinical relevance using a large in-house cohort with sufficient patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, ALKBH5 frequently has the opposite effect in CRC. ALKBH5 was significantly downregulated in human CRC tissues and loss of ALKBH5 predicted worse prognosis of CRC patients (66,67,70). Functionally, the knockdown of ALKBH5 enhanced the proliferation of colon cancer cells, while the overexpression of ALKBH5 suppressed this ability.…”
Section: Effects Of Alkbh5 On Crcmentioning
confidence: 97%
“…Functionally, the knockdown of ALKBH5 enhanced the proliferation of colon cancer cells, while the overexpression of ALKBH5 suppressed this ability. Mechanistically, the ALKBH5-mediated m6A modification of PHF20 mRNA inhibited its stability, while the loss of ALKBH5 increased the stability of PHF20 mRNA and prolonged its half-life to facilitate CRC proliferation, colony formation, migration, and invasion (66). In addition, ALKBH5 cooperates with YTHDF3 to facilitate the degradation of circ3823, an oncogene that promotes proliferation and angiogenesis in CRC, and finally inhibits CRC progression.…”
Section: Effects Of Alkbh5 On Crcmentioning
confidence: 99%